Synthesis, structural characterization and magnetic properties of the monoclinic ordered double perovskites BaLaMSbO6, with M = Mn, Co and Ni - Blanco, M. Cecilia; De Paoli, Juan M.; Ceppi, Sergio; Tirao, Germán Alfredo; Nassif, Vivian M.; Guimpel, J.; Carbonio, Raúl E. (2022)
Fil: Blanco, M. Cecilia. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Fisicoquímica; Argentina.